Nilai Tukar, Keterbukaan Ekonomi dan Kinerja Pertumbuhan Ekonomi Di Indonesia - Suhendra, Indra (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
This paper is conducted to answer whether the performance of economic growth is significantly influenced by the exchange rate and economic openness in Indonesia. To answer this question, we apply a multiple regression model for 48 annual data for the period 1971 to 2019. We used index numbers to measure economic growth performance based on references from the ICRG Risk Rating System, PRS Group, in assessing macroeconomic performance around the world. We also differentiate the exchange rate variable into LNERt and LNERt-1 to determine whether there is a difference between the two in affecting economic performance growth performance. The results showed that LNERt had a negative effect on economic growth, while economic openness and LNERt-1 had a positive and significant effect on Indonesia's economic growth performance. The recommendation of this study is that increasing trade competitiveness is important in the long run, especially in order to maximize the benefits of economic openness. Then, it is also important to ensure that future exchange rate volatility does not have a negative impact on economic growth performance